Peran Aparatur Pemerintah Dalam Pemberdayaan Organisasi Kepemudaan Dikelurahan Mangalli Kecamatan Pallangga Kabupaten Gowa - Fahira, Jihan; Mahsyar, Abdul; Haerana, Haerana (Universitas Muhammadiyah Makassar, 2021)
This study purposed to find out how the role of government officials in empowering youth organizations in Mangalli Village, Pallangga District, Gowa Regency. This study used descriptive qualitative research. The number of informants in this study amounted to 8 people. The data collection techniques were the instruments of interview, observation and document analysis. The results showed that the role of government officials had not been maximally seen from three indicators, the first was as a motivator, the local government was not carrying out its role because it provided verbal support or without direct meetings with organizational members, which could be a motivation to be more enthusiastic about carrying out activities -activity. secondly, as a communicator, the local government carried out its role quite well because it maintained and provided information related to the agenda or activities to be carried out even though via telephone or short message. Third, as a facilitator, the local government was very lacking in carrying out its role Keywords: The role of government officials, organizational empowerment.